PKMζ drives spatial memory reconsolidation but not maintenance - de Oliveira, João Rodrigo; Rossato, Janine I.; Souza, Johseph P. G.; Orvate, Rodrigo; Carneiro, Livia; Baracho, Ana Luizi; Cammarota, Martín (Frontiers in Synaptic Neuroscience, 2025)
Non-reinforced reactivation destabilizes spatial memory in the Morris water maze (MWM), triggering reconsolidation, a protein synthesis-dependent process that restabilizes reactivated memories. PKMζ is a constitutively active, atypical PKC isoform implicated in memory storage. However, the potential involvement of this kinase in spatial memory reconsolidation remains unexplored. We found that intra-dorsal CA1 infusion of the PKMζ inhibitor myristoylated ζ-inhibitory peptide (ZIP), but not its inactive scrambled analog scZIP, following non-reinforced spatial memory reactivation in the MWM, induced time-dependent, long-lasting amnesia in adult male Wistar rats. This effect was replicated by silencing PKMζ mRNA translation with phosphorothioated antisense oligonucleotides, but not by inhibiting the related PKCι/λ with ICAP, and was prevented by disrupting hippocampal GluN2B-NMDAR signaling with RO25-6981, proteasome activity with clasto-lactacystin β-lactone, and AMPAR endocytosis with dynasore hydrate. ZIP had no effect on retention when given without reactivation or after reinforced reactivation. These findings suggest hippocampal PKMζ is necessary for spatial memory reconsolidation in the MWM, but not for its passive maintenance.